A revised phylogenetic classification of the ant subfamily Formicinae (Hymenoptera: Formicidae), with resurrection of the genera Colobopsis and Dinomyrmex - Ward, Philip S.; Blaimer, Bonnie B.; Fisher, Brian L. (Zootaxa, 2016)
The classification of the ant subfamily Formicinae is revised to reflect findings from a recent molecular phylogenetic study and complementary morphological investigations. The existing classification is maintained as far as possible, but some tribes and genera are redefined to ensure monophyly. Eleven tribes are recognized, all of which are strongly supported as monophyletic groups: Camponotini, Formicini, Gesomyrmecini, Gigantiopini, Lasiini (= Prenolepidii syn. n.), Melophorini (= Myrmecorhynchini syn. n.; = Notostigmatini syn. n.), Myrmelachistini stat. rev. (= Brachymyrmicini syn. n.), Myrmoteratini, Oecophyllini, Plagiolepidini, and Santschiellini stat. rev. Most of the tribes remain similar in content, but the generic composition of Lasiini, Melophorini, and Plagiolepidini is changed substantially. Species that have been placed in the genus Camponotus belong to three separate lineages. To ensure monophyly of this large, cosmopolitan genus we institute the following changes: Colobopsis and Dinomyrmex, both former subgenera of Camponotus, are elevated to genus level (stat. rev.), and two former genera, Forelophilus and Phasmomyrmex, are demoted to subgenus status (stat. n. and stat. rev., respectively) under Camponotus; two erstwhile subgenera of Phasmomyrmex, Myrmorhachis and Myrmacantha, become junior synonyms (syn. n.) of Camponotus (Phasmomyrmex); and the Camponotus subgenus Myrmogonia becomes a junior synonym (syn. n.) of Colobopsis. Dinomyrmex, represented by a single species from southeast Asia, D. gigas, is quite distinctive, but Camponotus and Colobopsis exhibit more subtle differences, despite being well separated phylogenetically. We identify morphological features of the worker caste that are broadly useful for distinguishing these two genera. Colobopsis species on the islands of New Caledonia and Fiji—regions with few native Camponotus species—tend to exceed these diagnostic bounds, but in this case regionally applicable character differences can be used to distinguish the two clades. Despite confusing similarities in the worker caste Colobopsis and Camponotus retain diagnostic differences in their larvae and pupae.